Self-care methods use for acne treatment among health science students - Sari Taha; Manal Taha; Sa’ed H. Zyoud (Exploratory Research in Clinical and Social Pharmacy)
Introduction: The use of self-care methods, such as over-the-counter (OTC) products and complementary and alternative medicine (CAM), is common along the acne care pathway. This study aimed to explore self-care methods for acne and assess their associations with acne severity. Methods: This cross-sectional study was conducted among university students in health programs. Convenience sampling was used to invite participants to complete a survey containing sociodemographic, clinical, and self-care-related questions. Acne diagnosis and severity were evaluated by a physician via the Global Acne Grading System (GAGS). A multivariate regression model was used to analyze the associations between variables. Results: The final sample comprised 190 participants, with 24.2 % males and 70.8 % females. Most participants had mild acne (77.4 %) and reported positive family histories (82.1 %). Approximately one-third used OTC products (31.1 %), and nearly two-thirds used CAM (62.6 %). The most frequently used OTC products were facial cleansers (48.2 %), followed by creams and moisturizers (30.7 %) and cleansing soap (21.1 %). A lack of acne severity was the primary reason for the use of CAM. Social media (46.7 %) and the internet (46.2 %) were the most frequently reported sources of information. Acne severity was associated with OTC product use (p = 0.009) and the duration of acne (p < 0.001). Furthermore, OTC product use was associated with receiving a professional diagnosis (p < 0.001). Conclusions: This study identified the most common OTC products and CAM used in acne and demonstrated an association between OTC product use and acne severity. Future studies should explore discussions on self-care methods in clinical consultations and the timing of using these methods throughout the care pathway. Integrating shared decision-making in clinical practice and tailoring educational interventions to patient preferences and communication channels may encourage the safe and effective use of self-care methods.